MODULUS ELASTISITAS BAMBU BETUNG DENGAN VARIABEL PANJANG - Rambu Ririnsia Harra Hau; Masturi Masturi; Ian Yulianti; Salvo Kahumbu Hau; Soleman Dappa Talu (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
The main issues that were examined in this study is the modulus of elasticity bamboo betung with variable length. The purpose of this study was to measure the modulus of elasticity on bamboo betung with variable. Modulus of elasticity in bamboo shows the flexibility for using in a various fields. In this study the bamboo is made into small girders with a uniform thickness and width are respectively 0.8cm and 1.5cm. The length of the bamboo that is used in this study are the 50cm, 60cm, 70cm, 80cm, 90 cm, 100cm. To determine the elasticity of the bamboo it is provided with a load in the middle position. From the research results obtained showing the longer bamboo the greater flexibility gained linearly elastic modulus is 1.0122E+10N/m2. Keywords: bamboo, girder, modulus of elasticity.